An evaluation of the clinical audit of diabetes management at community health centres in the metro district of the Western Cape Province - Govender, Indira (Department of Public Health and Family Medicine, 2014)
This study aimed to evaluate the long-term trend in quality improvement and determine whether there had been an increase in the performance of diabetic clinical processes.